Development and expert validation of a 'Data-to-Action Continuum' to measure and advance the data-use capabilities of national tuberculosis programs - Manish Kumar; Jeanne Chauffour; Meredith Silver; Yanira Garcia-Mendoza; David Boone (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background The Data-to-Action Continuum (D2AC) Toolkit is intended to advance the data use capabilities associated with people, processes, technology, and institutions of national tuberculosis programs (NTPs). It empowers NTPs and stakeholders to measure current capabilities, identify areas amenable to interventions to build future capacities, and helps align the TB information system to better achieve the NTP's goals. This paper describes the development process of the D2AC Toolkit, whose aim is to enable NTPs and stakeholders-especially the policymakers, program managers, and laboratory and facility managers-to precisely gauge the barriers limiting the use of data for action and devise appropriate interventions to address them. # Methods Building on a scientific and grey literature foundation, the D2AC Toolkit was collaboratively developed by a core group of the TB data, Impact Assessment and Communications Hub (TB DIAH) project. The Toolkit was validated by a group of international and country-level experts following an iterative and user-centered process employing mixed methods. # Results The expert-validated D2AC Toolkit measures appropriate capabilities required to transform data to action in the context of an NTP at the national, regional, district, and facility levels across five domains and 17 subdomains using a five-point Likert scale: nascent, defined, established, institutionalized, and optimized. # Conclusions The continuum describes the status of various domains and corresponding subdomains and enables the identification of future goals for each subdomain. The future capabilities are meant to guide the development of an improvement path toward the desired level of advancement and monitor progress toward the desired goals. By integrating an iterative and user-centered process and using mixed methods, the D2AC Toolkit enables policymakers, program managers, and service providers to gauge current capabilities, identify future priorities, and develop an implementation plan to improve the organizational ability to transform data to action for achieving tuberculosis program goals.